2018
DOI: 10.3390/computers7010012
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Provenance of Personal Data Using Comics

Abstract: Personal health data is acquired, processed, stored, and accessed using a variety of different devices, applications, and services. These are often complex and highly connected. Therefore, use or misuse of the data is hard to detect for people, if they are not capable to understand the trace (i.e., the provenance) of that data. We present a visualization technique for personal health data provenance using comic strips. Each strip of the comic represents a certain activity, such as entering data using a smartph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…All 17 studies were found in the SLR process together with the snowball technique, which are [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and are focused on managing provenance data in HISs. In Table 10 , the similarities of the 17 studies are observed in the following characteristics that contribute to the management of provenance data in HISs: use of models from the W3C PROV family; use of different models from the W3C PROV family; use of provenance techniques with blockchain; and use of provenance techniques with middleware.…”
Section: Similarities Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All 17 studies were found in the SLR process together with the snowball technique, which are [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and are focused on managing provenance data in HISs. In Table 10 , the similarities of the 17 studies are observed in the following characteristics that contribute to the management of provenance data in HISs: use of models from the W3C PROV family; use of different models from the W3C PROV family; use of provenance techniques with blockchain; and use of provenance techniques with middleware.…”
Section: Similarities Of the Selected Studiesmentioning
confidence: 99%
“…We highlight the data provenance models indicated by the W3C implemented through computational tools in different types of HISs. The models indicated by the W3C that appeared the most were as follows: PROV [ 91 , 96 , 98 , 99 , 103 , 105 , 106 ] applied in HISs (EHRs, PHRs, the LHS, the CRIS, and the HIS); PROV-O [ 91 , 95 , 96 , 98 , 99 ] applied in EHRs, PHRs, the LHS, and the CRIS; OPM [ 97 , 98 , 100 , 101 ] applied in HISs (PHR and LHS); PROV-DM [ 91 , 96 , 99 , 101 ] applied in HISs (HER, PHRs, and the CRIS); and PROV-N [ 98 , 99 ] applied in HISs (PHRs and the LHS). These models appear more frequently because they are application-specific models of data provenance recommended by the W3C, capable of describing the entities and processes involved in the production of a resource.…”
Section: Systematic Literature Review Reportmentioning
confidence: 99%
“…Maka disimpulkan bahwa komik mampu membantu siswa menaikkan literasi sains (Riwanto & Budiarti, 2020). Hal ini mampu ditunjukkan dari gambaran visual secara ikonik pada media komik (Schreiber & Struminksi, 2018). Sehingga peserta didik tidak langsung belajar memakai media konkret melainkan menggunakan gambar kartun yang menarik sebagai topik materi pembelajaran (Hartel & Dunst, 2019).…”
Section: Pendahuluanunclassified
“…In another study [18], each comic character forms the strip, which is represented as an activity, and the overall visualization was created by recording the provenance graphs. Data citation and provenance relationship, distinguished by a certain model to represent views of the citation, and their relation in query construct is presented in [19], followed by another paper, where authors presented an application that uses the combination of the provenance values and trust values of other observations to personalize their website content, hence creating a two-leveled model, by including provenance trust and observations of the system as well [20].…”
Section: Publications' Review and Research Findingsmentioning
confidence: 99%